2007
DOI: 10.1007/s00442-007-0794-z
|View full text |Cite
|
Sign up to set email alerts
|

Plastic responses to temporal variation in moisture availability: consequences for water use efficiency and plant performance

Abstract: The ability to appropriately modify physiological and morphological traits in response to temporal variation should increase fitness. We used recombinant hybrid plants generated by crossing taxa in the Piriqueta caroliniana complex to assess the effects of individual leaf traits and trait plasticities on growth in a temporally variable environment. Recombinant hybrids were used to provide a wide range of trait expression and to allow an assessment of the independent effects of individual traits across a range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 67 publications
4
71
0
Order By: Relevance
“…The ability to modify physiological traits in response to temporary variation can increase fitness (Picotte et al, 2007). Our study demonstrated that N. peltata developed a series of photosynthetic acclimation features to help the plant cope with temporary terrestrial habitats, which included less stomatal density, a smaller stomatal aperture area, lower E and g s , and high WUE.…”
Section: Discussionmentioning
confidence: 73%
“…The ability to modify physiological traits in response to temporary variation can increase fitness (Picotte et al, 2007). Our study demonstrated that N. peltata developed a series of photosynthetic acclimation features to help the plant cope with temporary terrestrial habitats, which included less stomatal density, a smaller stomatal aperture area, lower E and g s , and high WUE.…”
Section: Discussionmentioning
confidence: 73%
“…Additionally, among other traits, length‐width ratio of leaves was found exhibiting considerable plasticity in Piriqueta caroliniana Urban (Turneraceae), with narrower leaves being produced under more arid conditions in successive years (Picotte, Rhode, & Cruzan, 2009) or even in successive seasons of the same year (Picotte et al. 2007). However, as we lack measurements from natural habitats and our experiment has not been carried out under natural conditions in common gardens with Mediterranean and/or semidesert climate but under glasshouse/garden conditions with optimal supplies of water, light, and nutrients, the observed trends rather demonstrate that plants with provenances from semi‐arid habitats either have broader leaves or are capable to produce broader leaves than those from more mesic conditions when confronted with optimal growth conditions and that this trait or the plasticity of this trait is selected for.…”
Section: Discussionmentioning
confidence: 99%
“…One interpretation of the above result is that low WUE was advantageous for plants. An efficient use of water may help plants to survive persistent droughts in arid environments but be disadvantageous in seasonally dry and competitive habitats (Ehleringer 1993;Mediavilla and Escudero 2003;Nicotra and Davidson 2010;Picotte et al 2007;Sandquist and Ehleringer 2003). Alternatively, assuming that first-year leaf 5 C resulted from the seed-toleaf mobilization of C-enriched components, the increasing probability of survival of Q. pyrenaica as leaf 5 C decreased could be mostly reflecting a positive effect of first-year photosynthetic carbon gain on subsequent survival.…”
Section: Relevance Of Functional Traits For Survivalmentioning
confidence: 99%
“…Thus, maximizing net carbon assimilation relative to water loss, i.e. leaf water use efficiency (WUE), generally increases plant growth (Dudley 1996;Geber and Griffen 2003;Picotte et al 2007) and survival (Casper et al 2005;Ehleringer 1993) in these ecosystems. There are multiple ways in which seed size and dispersal microsite can affect leaf WUE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation